A higher activation threshold of memory CD8+ T cells has a fitness cost that is modified by TCR affinity during Tuberculosis - Carpenter, Stephen M (2016)
All relevant data are within the paper and its Supporting Information files except for the primary TCR sequences. The data files for the primary TCR sequences are publicly deposited in the University of Massachusetts Medical School’s institutional repository, eScholarship@UMMS. The permanent link to the data is http://dx.doi.org/10.13028/M2CC70